Drought in Nicosia using Standardized Precipitation Index SPI-n and BMDI drought index - Theophilou, Marios K.; Serghides, Despina Kyprianou (My University, 2015)
The number of rainy days per year in calculated to follow a negative trend in Nicosia and for that an analysis of drought using the Standardized Precipitation Index SPI-n and the BMDI drought index has been made. The calculations have been made using daily rainfall total amounts for the station of Nicosia for a long enough period in order to extract save conclusions about the drought trend. BMDI index has been specifically calculated for the case of Cyprus. The results show that throughout the years, Nicosia has experienced the results of drought, with extremely low precipitation amounts for some years and thus severe drought events.
Keywords: Climate change; Drought; Drought indices